2010
DOI: 10.1016/j.jtcvs.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular surgical restoration for anteroseptal scars: Volume versus shape

Abstract: When the main target of left ventricular surgical restoration is left ventricular reshaping rather than left ventricular volume reduction, early and late outcomes seem to improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…| 305SVR improves HF symptoms and long-term survival for patients with ischemic cardiomyopathy 3. The majority of cases in these studies underwent standard open-heart surgery via sternotomy with cardiopulmonary bypass, cardioplegic myocardial arrest, and ventriculotomy.…”
mentioning
confidence: 99%
“…| 305SVR improves HF symptoms and long-term survival for patients with ischemic cardiomyopathy 3. The majority of cases in these studies underwent standard open-heart surgery via sternotomy with cardiopulmonary bypass, cardioplegic myocardial arrest, and ventriculotomy.…”
mentioning
confidence: 99%
“…Because medication alone 16 or CABG alone 17 was not associated with satisfactory results in those with severe LV dilatation, acute reverse remodeling by SVR was expected to benefit such patients by reducing LV volume 18 and restoring LV shape. 19 Although a retrospective study with a relatively small sample size showed favorable results for SVR, 20 a large-scale trial (STICH) found there was no beneficial effect on survival in SVR plus CABG compared with CABG alone. 4 However, the validity of the STICH results is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The Dor procedure was performed on the basis of the recovery of predictable volume 1,2 . However, the restoration of the physiologic conical shape cannot be achieved by this method 3,4 . We, therefore, modified the ESP in an attempt to restore both the shape and volume.…”
Section: Commentmentioning
confidence: 99%